2019
DOI: 10.1590/1980-5373-mr-2018-0833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mass Loss in Different Stages of Printed Circuit Boards Recycling Employed in Temperature Controllers

Abstract: The aim of this work was to evaluate mass loss in each stage of the recycling process for metal recovery from PCBs of controllers and temperature indicators of cold chambers. The stages of process consists of grinding, particle size classification, magnetic and electrostatic separation. It was analyzed 13 kg of PCBs. These PCBs were crushed and ground. The ground material were subjected to magnetic and electrostatic separator. The losses in the comminution stages were 12.69 % and are lower than those found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The modern society is becoming more and more dependent on electronic devices, which are characterized by a short replacement cycle . This tendency can be translated in a growing flow of new technologies to the market with a consequent increase of an electronic waste amount (e-waste). , An amount of 45 million tons of e-waste was generated in 2016 with an estimated annual growth rate of 3–4%. There are four main sources of e-waste: small/large home appliances, hospital medical equipment, office machines, and industrial equipment/machines . Within the entire e-waste quantity, the WPCB percentage is relevant (3–6%). The WPCBs are composed for more than 40% (w/w) of metals. , Cu has an average concentration of 20% (w/w) of whole metals, and it is 10–40 times higher than that in copper-rich minerals. , The annual Cu production is around 15 million tons, and about 30% is used for the electric and electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…The modern society is becoming more and more dependent on electronic devices, which are characterized by a short replacement cycle . This tendency can be translated in a growing flow of new technologies to the market with a consequent increase of an electronic waste amount (e-waste). , An amount of 45 million tons of e-waste was generated in 2016 with an estimated annual growth rate of 3–4%. There are four main sources of e-waste: small/large home appliances, hospital medical equipment, office machines, and industrial equipment/machines . Within the entire e-waste quantity, the WPCB percentage is relevant (3–6%). The WPCBs are composed for more than 40% (w/w) of metals. , Cu has an average concentration of 20% (w/w) of whole metals, and it is 10–40 times higher than that in copper-rich minerals. , The annual Cu production is around 15 million tons, and about 30% is used for the electric and electronic devices .…”
Section: Introductionmentioning
confidence: 99%
“…By individual components, there is a prevalence of studies on PCBs (53 studies out of 93, 57%). The high concentration of base metals (mainly copper) and the presence of precious and critical metals are notable in these components (Table 1) and justify the preference for authors to address PCBs (D’Adamo et al, 2019; Schneider et al, 2019). For batteries, 31 studies were found (33.3%).…”
Section: Recyclingmentioning
confidence: 99%